MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATA PELAJARAN IPA ENERGI BUNYI KELAS IV SDN II PULE TAHUN AJARAN 2017/2018 - Ribud Setiawan; Happy Susanto; Ayok Ariyanto (TARBAWI:Journal on Islamic Education, 2019)
Classroom action research (CAR) aims to improve student learning achievement by using the snowball throwing learning model on sound energy science subjects, knowing the implementation of learning using the Snowball Throwing learning model, improving and improving student learning achievement using the Snowball Throwing learning model on Sound Energy Science class IV grade SDN II Pule 2017/2018 academic year. Primary school-oriented education, there needs to be renewal and innovation in the teaching process so as not to just record, listen, lecture and so on. As is the case in the State Primary School (SDN) II Pule, in the learning process it is still recording, listening to lectures, therefore changes need to be held. Based on the results of the Classroom Action Research conducted at Pule SDN II Trenggalek, the implementation of the first cycle of action I that has been carried out has not yet obtained maximum results, with completeness of 40% and has not met the KKM value standards. Next, the researcher conducted cycle I of action II, with completeness of 60%. Then do the second cycle of action I which gets 80% completeness, and cycle II action II with 100% completeness. Thus it can be concluded that the use of the Snowball Throwing learning model can improve learning outcomes in the Natural Sciences "Sound Energy" class at grade IV SDN II Pule, Pule Village, Pule District, Trenggalek Regency.